Hot spotting surgical patients undergoing hepatopancreatic procedures. Issue 6 (June 2019) - Merath, Katiuscha; Chen, Qinyu; Johnson, Morgan; Mehta, Rittal; Beal, Eliza W.; Dillhoff, Mary; Cloyd, Jordan; Pawlik, Timothy M.
Abstract: Background: The burden of health care spending in the United States is a major concern, as health care costs have exponentially increased during the last three decades. The objective of the current study was to investigate the degree of cost-concentration among Medicare patients undergoing liver and pancreatic surgery. Methods: Medicare claims data from 2013 to 2015 were used to identify patients undergoing elective liver and pancreatic resections. Patients were divided into four groups: 1) non-complex pancreatic procedures; 2) complex pancreatic procedures; 3) non-complex liver procedures; and 4) complex liver procedures. Unadjusted price-standardized Medicare payments were calculated and payments were divided into quintiles. Patient-level factors associated with payments were analyzed by multivariable linear regression. Results: A total of 17, 125 patients were included in the study. Patients in the top quintile of spending accounted for over 40% of payments for all liver and pancreatic procedures. Patients with comorbidity scores ≥5, male sex, open surgical approach and a diagnosis of congestive heart failure were associated with higher costs. Conclusion: Patients undergoing liver and pancreatic resections on the top 20% of payments were responsible for a disproportionate share of Medicare payments – over 40% of total expenditures. Overall hospital surgical volume was lower among the highest quintile of payments.